Peroxisome Proliferator-Activated Receptors (PPARs) as Potential Inducers of Antineoplastic Effects in CNS Tumors - Lars Tatenhorst; Eric Hahnen; Michael T. Heneka (PPAR Research)
The peroxisome proliferator-activated receptors (PPARs) are ligand-inducible transcription factors which belong to the superfamily of nuclear hormone receptors. In recent years it turned out that natural as well as synthetic PPAR agonists exhibit profound antineoplastic as well as redifferentiation effects in tumors of the central nervous system (CNS). The molecular understanding of the underlying mechanisms is still emerging, with partially controverse findings reported by a number of studies dealing with the influence of PPARs on treatment of tumor cells in vitro. Remarkably, studies examining the effects of these drugs in vivo are just beginning to emerge. However, the agonists of PPARs, in particular the thiazolidinediones, seem to be promising candidates for new approaches in human CNS tumor therapy.